Peran Ekonomi Digital dalam Meningkatkan Daya Saing UMKM di Kota Medan - Meri Roito Siregar; Laisa Asri Nasution; Mawar Rasimah Br. Dalimunthe; Mohamad Anouvan Syumantra; Nurbaiti Nurbaiti (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2026)
This study aims to analyze the role of the digital economy in increasing the competitiveness of MSMEs in Medan City. The rapidly developing digital transformation provides opportunities for MSMEs to expand their markets, improve operational efficiency, and strengthen their competitive position. However, the use of digital technology among MSMEs in Medan remains limited due to low digital literacy, limited capital, lack of training, and minimal use of digital platforms such as e-commerce, social media, and Google My Business. This study uses a descriptive qualitative method through a literature review of research conducted in 2024–2025. The results of the analysis indicate that the digital economy plays a significant role in increasing the competitiveness of MSMEs, particularly through digital marketing, technological innovation, and optimization of digital platforms that can increase visibility and interaction with customers. Based on the Resource-Based View (RBV) approach, the competitive advantage of MSMEs is determined by the quality of internal resources, especially digital literacy, innovation capabilities, and technology management. With the support of training and government policies, the implementation of the digital economy has the potential to strengthen the growth and sustainability of MSMEs in Medan City.